Dysodiles from the lower Barremian of Lebanon: Insights on the fossil assemblages and the depositional environment reconstruction. (April 2021) - El Hajj, Layla; Baudin, François; Gèze, Raymond; Cavin, Lionel; Dejax, Jean; Garcia, Géraldine; Horne, David J.; Maksoud, Sibelle; Otero, Olga; Azar, Dany
Abstract: The Recent re-/discovery of unusual Lower Cretaceous continental deposits (dysodiles) brings important and exceptional paleontological assets. Dysodile beds are found in many localities across Lebanon and are characterized by their high organic matter content and their richness in exceptionally well-preserved fossils. We focus our study on five sampling localities in the lower Barremian sandstone beds, deposited when Lebanon was located in the north-eastern part of the Gondwana supercontinent. The localities are found associated with volcanic deposits suggesting a close relation between volcanism and their deposition and/or preservation. The present study provides, for the first time, insights on the fossil assemblages found in the dysodiles, including fishes, turtles, gastropods, insects, plant debris (macroflora and palynomorphs), ostracods and coprolites. We provide a preliminary reconstruction of the depositional environment that is common to the five sampling localities. It was a freshwater lake or possibly a series of interconnected lakes, in the vicinity of volcanic edifices, surrounded by a typical Lower Cretaceous flora (open forest environment), and inhabited by basal actinopterygian fishes and teleosts that will constitute the core of subsequent freshwater assemblages. The Lebanon localities have important implications for local palaeoenvironments as well as worldwide biogeography. In addition, the fossil assemblages show some taxonomic and taphonomic differences between the sampling sites, suggesting local differences in environmental conditions during deposition. Graphical abstract: Image 1 Highlights: New continental Konservat-Lagerstätte from the lower Barremian of Lebanon. Contribution to the knowledge of the lacustrine flora and fauna of north-eastern Gondwana. Palaeoenvironmental reconstruction of the lacustrine Lebanese lower Barremian.